Development of market opportunities and increasing economic value of Sambal Uleg Petis Pantura in Samarinda - Khoirul Amin; Devy Indah Paramitha; Gilang Mukti Rukmana (Universitas Muhammadiyah Magelang, 2024)
Sambal, a culinary product, epitomizes the national identity of the Indonesian people. Virtually every region in Indonesia boasts its own chili sauce, reflecting its unique social and cultural identity. One such example is sambal uleg from Lamongan Regency, renowned for its distinctive flavor derived from petis, a key ingredient exclusively found in the north coast areas of Lamongan and Tuban. This unique taste renders sambal petis pantura a potential culinary gem, particularly in Samarinda, where the populace savors spicy and savory dishes. However, several challenges hinder the development of typical Pantura sambal uleg products. This service aims to capitalize on market opportunities and enhance the economic value of processed Pantura chili products in Samarinda City. The method employed is mentoring, comprising three stages: preparation, implementation, and evaluation. The outcomes of this service initiative include expanded market outreach, increased economic value of the developed products, issuance of partner business permits, and halal certification.